MEDICINAL PLANT EXTRACTS USED FOR BLOOD SUGAR AND OBESITY THERAPY SHOWS EXCELLENT INHIBITION OF INVERTASE ACTIVITY: SYNTHESIS OF NANOPARTICLES USING THIS EXTRACT AND ITS CYTOTOXIC AND GENOTOXIC EFFECTS : Pharmaceutical Science-Pharmacology - D’BRITTO, VIRGINIA; PUSHPARANI DEVI, PHILEM; B. L. V. PRASAD; DHAWAN, ALOK; MANTRI, VIVEK G.; PRABHUNE, ASMITA (International Journal of Life Science and Pharma Research, 2012)
Extract of Azardirecta indica, Cephalandra indica, Calotropis procera and Syzygium jambolanum, prepared together, is an elixir for the treatment of blood sugar and obesity in homoeopathic medicine. Like many other homeopathic elixir, the exact mechanism of action of this popular elixir is also still unknown. It is known that inhibitors of α-glucosidases such as invertase, α amylase etc, can delay the digestion and adsorption of carbohydrates, thereby, inhibiting post prandial hyperglycemia and thus helps in Diabetes therapy. In our present study , the invertase inhibitor action of the elixir was tested in order put more light on the therapeutic machanism of this elixir. Moreover, rapid bio-reduction of Au3+ and Ag+ ions to their respective nanoparticles was achieved using the same extract of these medicinal plants. Cytotoxicity (MTT assay) and genotoxicity (COMET assay) experiments have been performed on these nanomaterials. Invertase inhibition activity was excellent. MTT results proved the bio-compatible nature of these biochemically synthesized gold and silver nanoparticles upto 10-4M concentration towards HepG2 cells. At higher nanoparticle concentration (10-3M or above), DNA damage occurred which was very easily detected by COMET assay. The overall study suggested that these biogenic metal nanoparticles are non-cytotoxic and non-genotoxic upto 10-4M.